2006
DOI: 10.1091/mbc.e05-11-1065
|View full text |Cite
|
Sign up to set email alerts
|

Type I Collagen in Hsp47-null Cells Is Aggregated in Endoplasmic Reticulum and Deficient in N-Propeptide Processing and Fibrillogenesis

Abstract: Heat-shock protein of 47 kDa (Hsp47) is a molecular chaperone that recognizes collagen triple helices in the endoplasmic reticulum (ER). Hsp47-knockout mouse embryos are deficient in the maturation of collagen types I and IV, and collagen triple helices formed in the absence of Hsp47 show increased susceptibility to protease digestion. We show here that the fibrils of type I collagen produced by Hsp47 ؊/؊ cells are abnormally thin and frequently branched. Type I collagen was highly accumulated in the ER of Hsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
149
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 51 publications
24
149
0
1
Order By: Relevance
“…The milder pheno type in humans probably results from residual serpin H1 function. Serpinh1-null mice are embryonically lethal 69 , owing to aggregation of improperly folded collagen in the rER, delayed collagen secretion and eventually defective collagen fibrillogenesis 70 .…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…The milder pheno type in humans probably results from residual serpin H1 function. Serpinh1-null mice are embryonically lethal 69 , owing to aggregation of improperly folded collagen in the rER, delayed collagen secretion and eventually defective collagen fibrillogenesis 70 .…”
Section: Box 1 | Classification Of Osteogenesis Imperfectamentioning
confidence: 99%
“…Heat shock protein 47 (HSP47), a collagen-specific molecular chaperone, is essential for the biosynthesis and secretion of collagen molecules (Nagata 1996;Nagata et al 1986Nagata et al , 1988Ishida et al 2006;Nagai et al 2000;Sauk et al 1994). Previous studies of various experimental diseases affecting the lungs have shown that there is a close association between increased expression of HSP47 and excessive accumulation of collagen (Ishii et al 2003;Kakugawa et al 2004Kakugawa et al , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, fibroblasts without HSP47 produce collagen fibrils that are abnormally long and thin (Ishida et al, 2006). The collagen chaperone appears to have several roles in the precise manufacture of the collagen molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock protein 47 (HSP47) encoded for by SERPINH1 (OMIM *600943), is a collagenspecific chaperone expressed in all collagen-secreting cells. It binds to the procollagen triple helix and is required for the proper assembly of the triple helical procollagen molecules after the modification by the prolyl-3 hydroxylation complex (Ishida et al, 2006;Widmer et al, 2012;Duran et al, 2015). FKBP10 (OMIM 607063) encodes for FKBP65, a type I collagen chaperone present in the ER along with HSP47.…”
Section: Introductionmentioning
confidence: 99%